Språkrikedom skapar ett mångsidigt identitetsspektrum - Outakoski, Hanna (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
Being able to express oneself in writing in different languages broadens the ways in which one can choose to talk or write about things. Children and young adults that have learned sufficient writing skills and vocabulary in North Sami along a national majority language and English are quick to choose different perspectives, voice, mood and subjects of discussion depending on the language of the writing task. The greatest challenge for these multilingual children does not lie in learning of different languages, but instead in receiving the support and exposure to linguistic input that is needed in reaching well developed bilingualism and a good level of literacy in both or all languages. Finding the ways to secure the existence of both the cultural and the multilingual context from which the identity spectrum and voices of these multilingual children arise is of uttermost importance.